Neurosteroid withdrawal disrupts GABAergic system development in human cortical organoids: implications for preterm birth - Lacaille, Helene; Lebayle, Ekaterina; Corneo, Barbara; Vacher, Claire-Marie; Penn, Anna A. (Frontiers in Cellular Neuroscience, 2025)
Preterm birth substantially elevates the risk of neurological and cognitive disorders. Recent evidence suggests that the abrupt loss of placental support, particularly the cessation of neurotrophic and neuroprotective hormones, alters neurodevelopmental trajectories and may contribute to neurodevelopmental risk associated with prematurity. Our study investigates how the placental steroid hormone, allopregnanolone (ALLO), affects cerebral cortex development using human cortical organoid models. Our findings reveal that while ALLO exposure produces modest effects on overall cortical development, its withdrawal specifically disrupts GABAergic but not glutamatergic neuronal development. These results demonstrate that placental hormones, including ALLO, may target specific neuronal populations critical for cortical function, identifying potential therapeutic interventions following placental loss in human preterm neonates.